Studies of Aedes a egypti immune pathways in response to dengue virus infection: evaluation of genetically modified mosquito fitness, immune pathway expression and natural genetic variation - Raban, Robyn, author; Olson, Ken, advisor; Black, William, committee member; Blair, Carol, committee member; Kondratieff, Boris, committee member (Colorado State University. Libraries, 2016)
Mosquito-borne diseases, such as dengue, are global health priorities, since they affect hundreds of millions of people per year. Vector control is one of the most successful tools for preventing mosquito-borne disease transmission and characterization of anti-viral mechanisms has led to the development of novel vector control strategies. One of the main mechanisms of mosquito antiviral defense is the small interfering RNA (siRNA) pathway, which has been shown to influence Aedes aegypti dengue viral infection. The RNA interference (RNAi) response of this pathway has been utilized to create transgenic Ae. aegypti lines, which are refractory to dengue virus type-2 (DENV2) infection. Additionally, genetic studies can also provide insights into function and natural variation of anti-viral pathways, potentially leading to the development of new approaches to vector control. The recent advancements in transgenic technologies are increasing the potential of genetically-modified vectors for disease management. In this project an RNAi based genetically-modified mosquito, Carb109, was evaluated for fitness after a backcrossing to a genetically diverse laboratory strain (GDLS). This method improved the mosquito fitness and transgene stability over previous non-backcrossed strains, making it more feasible for use in genetic vector control programs. However, positional effects of the transgene made the homozygote less fit and stable regardless of introgression into a GDLS. The next two aims explored the genetics of siRNA genes in a gene expression and a population genetic study. Gene expression of multiple potential anti-viral immunity genes in Ae. aegypti strains artificially selected for differences in midgut infection rates showed some evidence for the involvement of dicer2 (Dcr2), a siRNA gene in DENV2 midgut escape in these strains. Gene expression also varied naturally diurnally and over the lifetime of the mosquito, which demonstrated the importance of keeping consistent sample collection schedules for gene expression studies. Lastly, four non-synonymous substitutions in the Dcr2 gene were evaluated for association with susceptibility to DENV2 Jamaica 1409 infection, but no association was found.